Integrated transcriptome and metabolome analysis of melanin-related genes and metabolites in Muchuan Black Bones Chickens - Liu Wei; Jie Hong-Wei; Gao Ming-Chao; Yao Xiu-Mei; Yin Qiong; Xiang Hai; Ma Zheng; Zhang Zheng-Fen; Li Liang; Li Hua; Qi Hao; Ye Fei (PLoS ONE, 2025)
The Muchuan Black Bones Chickens represent a significant subtype of the Sichuan mountain black bones chickens. In the breeding of black bone chickens, the degree of melanization tends to separate due to hybridization, while molecular-assisted breeding techniques were still limited, and the key genes involved in melanin deposition in the early growth of black bones chickens have yet to be validated. Hypothesize that melanin deposition in Muchuan Black Bones Chickens was governed by specific genetic and metabolic regulators that can be systematically identified. This study aims to identify key genes and metabolites associated with melanin in Muchuan Black Bones Chickens through integrated transcriptomic and metabolomic analyses. CDP-ethanolamine, m-trigallic acid, UDP-4-dehydro-6-deoxy-D-glucose, glucoiberverin, and uridine diphosphate glucuronic acid (UDP glucuronic acid) were identified as significant differential metabolites, which were intimately linked to phenylalanine, tyrosine, and tryptophan biosynthesis associated with melanin accumulation. A total of 73 differentially expressed genes, including cAMP response element-binding protein 5 (CREB5) and GIPC PDZ domain containing family member 2 (GIPC2), were enriched in the neuroactive ligand-receptor interaction pathway, arginine-proline metabolism pathway, histidine metabolism, terpenoid backbone biosynthesis, and glycerophospholipid metabolism. This study identified significant metabolites and regulatory genes associated with melanin synthesis, establishing a theoretical foundation for the breeding and selection of chickens.